Shear and adhesion strength of open and closed system heat-treated wood samples - Can, Ahmet; Krystofiak, Tomasz; Lis, Barbara (Maderas. Ciencia y Tecnología, 2021)
This paper investigated the effects of heat treatment in open (atmospheric pressure) and a closed (under pressure) system on the shear and adhesion strength of Scots pine (Pinus sylvestris) wood. In addition, pull-off adherence testing was carried out of the coatings with water-based, polyurethane-based and oil/wax-based varnishes. Shear strength decreased significantly after heat treatment in Scots pine (31 % to 39 %) in open system, while it decreased between 2 % and 38% in the closed system without glue. The shear strength of the wood samples glued with glue was higher than the samples without glue at laboratory scale. The lower shear strength of modified wood could be attributed to other factors, such as the reduced chemical bonding or mechanical interlocking of adhesives, and the reduced strength of brittle modified wood substrate. With increasing heat treatment temperature adherence decreased. Maximum pull-off adhesion (4,80 MPa) was observed in the control samples coated with PUR.